Garbage enzyme as a solution to waste minimization - Ho, Yuek Ming; Ling, Leong Kee; Abd Manaf, Latifah (Springer, 2013)
Garbage enzyme is obtained by fermenting fruit and vegetable wastes. This alternative method of biological recovery of organic waste may provide a solution to waste minimization and reduction since a large proportion of municipal solid waste consists of food waste. A study was conducted to assess the implementation of garbage enzyme making and usage as an initiative to reduce the amount of municipal solid waste generated by a hawker community. It was found that practical values, communal spirit and awareness of environmental consequences were among the factors that encourage the practice of garbage enzyme making, while ignorance, time and convenience factors hinder garbage enzyme making and usage. Taking these factors into consideration, municipalities could promote garbage enzyme as a viable method in reducing the amount of MSW generated.